Extração de ácido lático pela técnica de membranas líquidas surfatantes : ensaios em bancada e em planta piloto - Juliana dos Santos Barbosa Coelho (2015)
In the present work, the extraction of lactic acid, by liquid surfactant membranes technique, from synthetic aqueous solutions that simulate the fermented mash, whose concentration is approximately 10%w/v, was studied. For this purpose, it was necessary to adapt the lactic acid dosage method proposed by the Brazilian Pharmacopeia (2010). It was observed that such a method can be adapted with good results, so that the process needed analyses can be carried out (solute determination in the external and in the internal phases), being possible to use a rest time of 10 minutes, higher or lower masses than those stipulated by the method (1 g), volumes instead of masses, lactic acid solutions with higher and/or basic concentrations, with sampling of, at least, 2 mL. Once the solute dosage method was determined, bench scale tests were carried out, verifying the influence of different permeation times, extractant concentration, internal phase concentration and composition (use of NaOH solutions rather than sodium acetate solutions), surfactant type and concentration (ECA®4360 e Infineum® C9268), diluent type and concentration (Escaid110, ExxsolD80 e ExxsolD100), and NaCl addition to the external phase to increase its ionic force. In these tests, a permeation time of 10 minutes, a concentration of Alamine® 336 extractant of 20% w/w, an internal phase constituted of 4mol.L-1 sodium hydroxide solution, and NaCl concentration of 1.2 mol. L -1 , equivalent to 30% of the NaOH concentration, used in the internal phase, were established as the best conditions, among the studied ones. The influence of NaCl addition to the external phase on the significant reduction of the primary emulsion swelling and on the increasing of solute extraction was observed. No significant difference was observed with respect to the diluent type. Among the investigated surfactants, practically, there was no variation with respect to the extraction percentage; swelling was greater with Infineum®C9268 as well as the enrichment content. The choice for its use was due to the higher ease of acquisition, with a concentration of 1% w/w. For the pilot scale tests, in a mechanically agitated column, the best extraction condition was obtained for a Fd/Fc = 1/1 ratio and total flow of Ft = 2 L.h-1 . For these conditions, a lactic acid extraction around 60%, an internal phase enrichment of 169%, a swelling of 27.3% and a 0.21% primary emulsion breakage were obtained.